Rebellion under the Banner of Islam - van Dijk, C. (Brill, 1981)
The Darul Islam rebellion, striving for the establishment of an Islamic State of Indonesia, broke out in several areas since 1949. The author describes each of these Darul Islam rebellions and identifies some of the factors which may help to explain their outbreak and persistence.
English
Keywords: Asian history; indonesia; Abdul Kahar Muzakkar; Aceh; Darul Islam (Indonesia); Republican Party (United States); Sekarmadji Maridjan Kartosuwiryo; West Java